Six new species of Otacilia from southern China (Araneae: Phrurolithidae) - Liu, Keke; Xu, Xiang; Xiao, Yonghong; Yin, Haiqiang; Peng, Xianjin (Zootaxa, 2019)
Six new ground sac spider species of the family Phrurolithidae were collected from southern China: Otacilia ailan sp. nov. (♀), O. daweishan sp. nov. (♂, ♀), O. fabiformis sp. nov. (♂, ♀) and O. jiandao sp. nov. (♀) from Hunan Province; and O. nonggang sp. nov. (♂, ♀) and O. yinae sp. nov. (♂) from Guangxi Zhuang Autonomous Region. All species are described and illustrated with photographs and line drawings.